Effect of Pressure Treatment on the Structure and Properties of Sintered Bronze; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Kurmangali D. K. (2015, 2015)
Title screen